IN SOCIAL PSYCHOLOGICAL STUDY NATION BUILDING INDONESIA SOCIAL GROUP STUDY IN NATIONAL INTEGRATION - Bernice Helena; Dea Denta Tajwidi (MAN Insan Cendekia Jambi, 2020)
The multidimension on international relations studies is hoped pushes the new idea to international relations student to analyze the international problem from any angle. The contribution of social psychology studies on international relations makes this study more acceptable. Conflict which is happened between state or intra state could be analysed by social psychology angle. Conflict caused by difference interest much of them there was no smooth communication on each party. Much of misperseption accured caused by the difference of norm, attitude and prejudice. In the state level, social conflict gives the influence on national integration. In this case, the political leader must do proactive action which is supported by mass. This is because integration is never ending process.